-3(x-3)+8(x-3)=6x+7-5x

Simple and best practice solution for -3(x-3)+8(x-3)=6x+7-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-3)+8(x-3)=6x+7-5x equation:


Simplifying
-3(x + -3) + 8(x + -3) = 6x + 7 + -5x

Reorder the terms:
-3(-3 + x) + 8(x + -3) = 6x + 7 + -5x
(-3 * -3 + x * -3) + 8(x + -3) = 6x + 7 + -5x
(9 + -3x) + 8(x + -3) = 6x + 7 + -5x

Reorder the terms:
9 + -3x + 8(-3 + x) = 6x + 7 + -5x
9 + -3x + (-3 * 8 + x * 8) = 6x + 7 + -5x
9 + -3x + (-24 + 8x) = 6x + 7 + -5x

Reorder the terms:
9 + -24 + -3x + 8x = 6x + 7 + -5x

Combine like terms: 9 + -24 = -15
-15 + -3x + 8x = 6x + 7 + -5x

Combine like terms: -3x + 8x = 5x
-15 + 5x = 6x + 7 + -5x

Reorder the terms:
-15 + 5x = 7 + 6x + -5x

Combine like terms: 6x + -5x = 1x
-15 + 5x = 7 + 1x

Solving
-15 + 5x = 7 + 1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-15 + 5x + -1x = 7 + 1x + -1x

Combine like terms: 5x + -1x = 4x
-15 + 4x = 7 + 1x + -1x

Combine like terms: 1x + -1x = 0
-15 + 4x = 7 + 0
-15 + 4x = 7

Add '15' to each side of the equation.
-15 + 15 + 4x = 7 + 15

Combine like terms: -15 + 15 = 0
0 + 4x = 7 + 15
4x = 7 + 15

Combine like terms: 7 + 15 = 22
4x = 22

Divide each side by '4'.
x = 5.5

Simplifying
x = 5.5

See similar equations:

| 10.7=d+43 | | 8+a+8+a=52 | | 23a=0 | | -16x^2-114x+14=0 | | 34+(-6)= | | -5x^2-30x=0 | | 4x(6-8x)+6=8 | | 14(2c+5)=-2c+9 | | 2-8(2d-1)=0 | | 9d-4d+1d+6=3d | | 6x+3=-3+3x+18 | | 7-2^3/6-4+2 | | 7x-11=15x | | 5x+2-2x-8=12-2x-3 | | 2s+5=6s+2 | | 3x+34=13-46 | | 15+-5= | | 100+(-55)= | | -p-2=9[2-3]+6 | | -21+x=x+16 | | f/3 | | 0=40-10y | | House+car=x | | 10x=4x-8x-7 | | 92782629=1638x | | 5x-44=-44 | | (-78)+45= | | 14y+1.5x=180 | | x-4+5-9x+14-7=5 | | 8+-11= | | -(5y+3)-(4y-8)=2 | | 11-6c-5=-12 |

Equations solver categories